Global Capital's 21st Century Repositioning Between COVID-19 and the Fourth Industrial Revolution on Africa - Makamani, Rewai; Makamani, Rewai; Nhemachena, Artwell (Langaa RPCIG, 2021)
What happens at the interface between Afrocentricity and COVID-19 is cause for wonder in a world that is anxious to short circuit global solidarity by trampling Pan-Africanism. Revolutions, including the Fourth Industrial Revolution, are rarely contextualised within the framework of Pan-Africanism and Afrocentricity even when they are celebrated as beneficial to the world. Interfacing Afrocentricity, COVID-19, Pan-Africanism and the Fourth Industrial Revolution, this book teases out the profound challenges of the 21st century. Calling for African solutions premised on African solidarity, the book critically engages the contemporary technological solutionism and technological evangelism that undergirds the Fourth Industrial Revolution and efforts to find vaccines for COVID-19. Unflinchingly interrogating these issues, the book is useful for scholars and activists in education, African languages, sociology, social anthropology, political science, history, religious studies, development studies, communication, medical sciences and legal studies.